In situ-generated arene-ruthenium catalysts bearing cycloalkylamines for the ring-opening metathesis polymerization of norbornene - Oliveira, Douglas P. [UNESP]; Cruz, Thais R. [UNESP]; Martins, Daniele M.; Maia, Pedro Ivo S.; Machado, Antonio E.H.; Bogado, André L.; Goi, Beatriz E. [UNESP]; Lima-Neto, Benedito S.; Carvalho-Jr, Valdemiro P. [UNESP] (Elsevier, 2020)
Arene-ruthenium complexes of type [RuCl2(p-cymene)(cyclo-alkylamine)], where alkyl is pentyl (1), hexyl (2), heptyl (3) or octyl (4), were successful synthetized and applied as pre-catalysts in ROMP of norbornene (NBE). From experiments as a function of temperature and NBE loads, the yields increased with increasing cyclo-alkyl ring size (4 > 3 > 2 > 1). This was associated with steric-electronic features of the amine ligands. The highest yields of polyNBE were obtained with [NBE]/[Ru] molar reaction ratio = 5000/1 in the presence of EDA at 50 °C for 60 min, with molecular weight range of 3.6–5.9 × 104 g mol−1 and Ð of 1.6–2.3. Characterization data obtained from CHN elemental analysis, spectroscopic techniques (FTIR, UV–vis, and 1H- and 13C{1H} NMR), cyclic voltammetry, computational studies, and single crystal diffraction for complexes 2 and 4 were useful for understanding the pre-catalyst behavior. Thermodynamic parameters from DFT-calculation corroborate a ROMP process via a dissociative mechanism.
Keywords: Ancillary ligands; Cycloalkylamines; DFT study mechanism; Norbornene; ROMP; Ruthenium